Asuhan Keperawatan Jiwa Pada Pasien Dengan Halusinasi Pendengaran Di Wisma Cendrawasih RSJ PROF. DR. HB SA’ANIN Padang Tahun 2026 - Zelfaisy Resfa Ramadhina; Dwi Happy Anggia Sari; Vivi Yuderna; Ramaita . (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Mental disorders are conditions in which individuals experience disturbances in thought patterns, behavior, and emotional responses that affect their ability to carry out daily activities. One of the most common mental disorders is schizophrenia with symptoms of auditory hallucinations. This study aimed to implement psychiatric nursing care for patients with auditory hallucinations at Cendrawasih Ward, Prof. Dr. HB Sa’anin Mental Hospital Padang in 2026. The method used was a case study approach through the nursing process, including assessment, nursing diagnosis, intervention, implementation, and evaluation. The case study was conducted over six days from February 4 to February 10, 2026, involving one patient with the primary problem of auditory hallucinations. The assessment results showed that the patient experienced auditory hallucinations characterized by talking and laughing alone, hearing voices without real stimuli, social withdrawal, and difficulty controlling the hallucinations. The main nursing diagnosis was auditory hallucinations with a secondary diagnosis of self-care deficit. It can be concluded that the implementation strategy (SP) was effective in helping the patient control auditory hallucinations. It is expected that the results of this study can serve as a guideline for improving the quality of psychiatric nursing care services, especially for patients with auditory hallucinations.